A Capsid Virus-Like Particle-Based SARS-CoV-2 Vaccine Induces High Levels of Antibodies and Protects Rhesus Macaques - Volkmann, Ariane; Koopman, Gerrit; Mooij, Petra; Verschoor, Ernst J.; Verstrepen, Babs E.; Bogers, Willy M. J. M.; Idorn, Manja; Paludan, Søren R.; Vang, Søren; Nielsen, Morten A.; Sander, Adam F.; Schmittwolf, Carolin; et al. (Frontiers in Immunology, 2022)
SARS-CoV-2 has caused a world-wide pandemic. Here, we present non-human primate immunogenicity and protective efficacy data generated with the capsid virus-like particle (cVLP)-based vaccine ABNCoV2 that has previously demonstrated immunogenicity in mice. In rhesus macaques, a single vaccination with either 15 ug or 100 ug ABNCoV2 induced binding and neutralizing antibodies in a dose dependent manner, at levels comparable to those measured in human convalescents. A second vaccine administration led to a >50-fold increase in neutralizing antibodies, with 2-log higher mean levels in the 100 ug ABNCoV2 group compared to convalescent samples. Upon SARS-CoV-2 challenge, a significant reduction in viral load was observed for both vaccine groups relative to the challenge control group, with no evidence of enhanced disease. Remarkably, neutralizing antibody titers against an original SARS-CoV-2 isolate and against variants of concern were comparable, indicating a potential for broad protection afforded by ABNCoV2, which is currently in clinical testing.